Estándares de calidad y su aplicación en el proyecto del laboratorio de investigación de ciencias de la computación en CIIDEA-Espam-MFL - Mendoza Marcillo, Ena Katherine (2016)
The purpose of this research was a study of quality standards in the project Research Laboratory in Computer Science CIIDEA-ESPAM-MFL, the same as stating a Quality Management System. For this systematization of the norms and standards studied was performed, then it analyzed its applicability in the department in question; using the literature method, comprising three phases are: accumulation of references, selection of references and signed. In the first phase, we investigated and collected the necessary information on the standards of national and international quality. a matrix which contains the data for the development of the work was then performed. the art of the interview with the future head of the Laboratory was then applied, this instrument helped that the authors know important issues in the department. And with all the information it obtained it was possible to use specific standards for the production of work. Finally, a tool that allowed internal evaluation which was a record-oriented internal control standards and quality standards, containing each of the services that will be offered Research Laboratory was developed. Together tab findings detection was also performed in order to find the faults that contain the organization when implementing the ISO 9001: 2015. Performing a preliminary analysis in an organization to implement a system, it means that compliance requirements are feasible.